Pengaruh Gaji dan Intensif Terhadap Kinerja Karyawan Nonmedis dan Perawat pada Klinik Rumah Luka di Kabupaten Sidoarjo - Dina Indriani; Budi Wahono; Alfian Budi Primanto (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
Abstract          Klinik Rumah Luka Sidoarjo is a center treatment of wounds and circumcision modern located in Sidoarjo and has been equipped with power medical professional, but there are obstacles that cause employees home Luka Sidoarjo less than optimal in be work that is permasalahn salary. One of them is late payroll and often times the calculation of salaries are not appropriate between the salaries of the principal and salary overtime . The purpose of this research is to determine the effect of salary and intensified towards the performance of the employees inKlinik Rumah Luka. This study is using a type of quantitative research associative with the method descriptive. The population that used as many as 36 people. The data analysis method used in this research is multiple linear regression (multiple regressions). The results of this study are salaries and incentives have a simultaneous and partial effect on employee performance at the Klinik Rumah Luka Sidoarjo . Keywords: Employee Salary; Employee Intensive; Employee Performance